2016
DOI: 10.1183/13993003.01504-2015
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and survival of idiopathic pulmonary fibrosis from national data in Canada

Abstract: Idiopathic pulmonary fibrosis (IPF) is a rare disease, with estimates of prevalence varying considerably across countries due to paucity in data collection. The aim of this study was to investigate the prevalence and incidence of IPF in Canada using administrative data requiring minimal extrapolation.We used mandatory national administrative data from 2007-2011 to identify IPF cases of all ages with an International Classification of Diseases (Version 10, Canadian) diagnosis code of J84.1. We used a broad defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
93
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(107 citation statements)
references
References 14 publications
6
93
1
7
Order By: Relevance
“…However, it is also possible that precise codes in these datasets may not capture all cases of IPF. One study from Italy reported a higher incidence of IPF after review of additional case records than when using coding criteria alone [15], yielding a very similar result for the narrow case definition to that obtained by HOPKINS et al [12] in the current study.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…However, it is also possible that precise codes in these datasets may not capture all cases of IPF. One study from Italy reported a higher incidence of IPF after review of additional case records than when using coding criteria alone [15], yielding a very similar result for the narrow case definition to that obtained by HOPKINS et al [12] in the current study.…”
supporting
confidence: 78%
“…Nevertheless, accepting potential variation in clinical practice and coding, the application of a specific ICD-10 code clearly suggests a fibrotic interstitial lung disease that may well be IPF or something very similar, and this was more common in the study by HOPKINS et al [12] than many other studies. This may reflect missed cases elsewhere, but the fact that some studies have taken a similar approach and still yielded lower incidences [22,23] suggests there may well be true differences in IPF incidence across regions.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Based on a recent systematic review [2], global IPF incidence is 3-9 cases per 100 000 per year in Europe and North America with increasing incidence over time. A similar incidence, 9 cases per 100 000, was reported in Canada using a narrow definition of IPF [3]. The age-adjusted mortality rate for IPF ranges from 2 to 10 per 100 000, resulting in an estimated 30 000-60 000 deaths in Europe in 2014 [4].…”
mentioning
confidence: 66%